Advances in antiviral strategies targeting mosquito-borne viruses: cellular, viral, and immune-related approaches - Ayyaz Khan; Zakirullah; Shahid Wahab; Seong-Tshool Hong (Virology Journal)
Abstract Mosquito-borne viruses (MBVs) are a major global health threat, causing significant morbidity and mortality. MBVs belong to several distinct viral families, each with unique characteristics. The primary families include Flaviviridae (e.g., Dengue, Zika, West Nile, Yellow Fever, Japanese Encephalitis), transmitted predominantly by Aedes and Culex mosquitoes; Togaviridae, which consists of the genus Alphavirus (e.g., Chikungunya, Eastern and Western Equine Encephalitis viruses), also transmitted by Aedes and Culex; Bunyaviridae (recently reorganized), containing viruses like Rift Valley Fever and Oropouche virus, transmitted by mosquitoes and sometimes sandflies; and Reoviridae, which includes the genus Orbivirus (e.g., West Nile and Bluetongue viruses), primarily affecting animals and transmitted by mosquitoes and sandflies. Despite extensive research, effective antiviral treatments for MBVs remain scarce, and current therapies mainly provide symptomatic relief and supportive care. This review examines the viral components and cellular and immune factors involved in the life cycle of MBVs. It also highlights recent advances in antiviral strategies targeting host factors such as lipid metabolism, ion channels, and proteasomes, as well as viral targets like NS2B-NS3 proteases and nonstructural proteins. Additionally, it explores immunomodulatory therapies to enhance antiviral responses and emphasizes the potential of drug repurposing, bioinformatics, artificial intelligence, and deep learning in identifying novel antiviral candidates. Continued research is crucial in mitigating MBVs’ impact and preventing future outbreaks.